Passive and active immunization against respiratory syncytial virus for the young and old - Tonya Villafana; Judith Falloon; M. Pamela Griffin; Qing Zhu; Mark T. Esser (Taylor & Francis Group, 2017)
Introduction: Respiratory syncytial virus (RSV) is the leading cause of lower respiratory tract infections in infants worldwide and also causes significant disease in the elderly. Despite 60 years of RSV research and vaccine development, there is only one approved medicine to prevent RSV infections. Palivizumab, a monoclonal antibody (mAb) against the RSV fusion (F) protein, is indicated for preterm infants and children at high-risk for RSV infections. It is an active time in RSV vaccine and mAb development with 14 vaccines and 2 mAbs currently being tested in clinical trials as of 13 February 2017. Active vaccination of women in the third trimester or passive immunization of infants with a mAb are particularly attractive approaches as the most severe disease occurs within the first 6 months of life. Areas covered: Here, we review current approaches for preventing RSV in the young and old, describe proposed clinical endpoints for studies in pediatric and adult clinical trials and highlight results from recent and ongoing clinical studies. Expert commentary: With 16 candidates in clinical development, approval of the first RSV vaccine or mAb for the prevention of RSV in all infants or the elderly is likely to occur in the next five years.